ANALISIS KADAR TIMBAL (Pb) DAN HEMOGLOBIN (Hb) PADA OPERATOR SPBU DI KOTA PEKANBARU DAN POTENSINYA SEBAGAI RANCANGAN HANDOUT DALAM PEMBELAJARAN BIOLOGI DI SMA - Khairunisa '; Yustina '; Darmadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to know the levels of lead (Pb) and Hemoglobin (Hb) in gas station’s operator in the city of Pekanbaru on May-July 2016. This research is descriptive research with cross sectional approach. This study consists of two phases i.e. phase analysis of the levels of lead (Pb) and Hemoglobin (Hb) in gas station operator in the laboratory and stage the draft Handout. Research samples taken with purposive sampling method with predetermined criteria. The sample of this research totalled 25 people consists of 18 men and seven women taken from a five gas station in the city of Pekanbaru.. Examination of the levels of lead (Pb) is done using AAS (Atomic Absorption Spectrophotometer) and examination of the levels of Hemoglobin (Hb) using the Easy Touch GCHb. Research results obtained from the 25 people who examined 15 people (60%) have a high lead levels and low hemoglobin levels. Research results are then used as material enrichment on teaching biology in senior high school class X on the air pollution material in the form of a Handout design.Key Words: Lead (Pb), Hemoglobin (Hb), Gas stasion’s operator, Handout.